Adhesion of tissue glues to different biological substrates†. (15th September 2016) - Bochyńska, A.I.; Hannink, G.; Buma, P.; Grijpma, D.W.
Abstract : Tissue adhesives are attractive materials with potential to replace the use of sutures and staples in the repair of the injured tissues. The research field of tissue adhesives is dynamically growing, and different methods and tissue models are employed to evaluate the adhesive properties of newly developed materials. It is thus difficult to directly compare the properties of materials developed by researchers from different groups. Moreover, the extrapolation of results obtained using different tissue models to the targeted human tissues is often not possible. Therefore, the purpose of the current study was to evaluate the adhesive properties of the three different tissues adhesives: the clinically used Dermabond® and fibrin glues, and the recently developed isocyanate‐terminated three‐armed adhesive block copolymers. Different biological substrates were used to assess their adhesion strengths: bovine Achilles tendon, meniscus tissue and skeletal muscle, chamois leather, and collagen films. Comparisons of the adhesive properties of the glues with these substrates were made. The obtained results were analyzed in terms of the chemistry and the adhesion mechanisms of the glues, and the composition and properties of the substrates like their hydrophilicity and surface morphology. We conclude that standardized procedures and models should be developed to allow direct comparison between the different (developed) tissue adhesives and to enable extrapolation of the results towards the targeted human tissues. Copyright © 2016 John Wiley & Sons, Ltd.